Are Inflammatory Biomarkers Increased in Varicose Vein Blood?. (October 2016) - Lattimer, Christopher R.; Kalodiki, Evi; Geroulakos, George; Hoppensteadt, Debra; Fareed, Jawed
Objectives: To test for the presence of inflammatory biomarkers in blood taken from varicose veins versus antecubital blood of the same patient and compare this to levels in healthy controls. Methods: Using a multiplex biochip array method (Randox, United Kingdom), the interleukins (ILs) IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, and IL-10; vascular endothelial growth factor; interferon γ, tumor necrosis factor α ; monocyte chemotactic protein 1 (MCP-1); and epidermal growth factor were measured in citrated plasma samples drawn from the arms and legs of 24 patients with varicose veins and 24 controls. Results: Expressed as median (interquartile range) in pg/mL, leg samples from patients with varicose veins had significantly higher levels of IL-8 and MCP-1 compared to their own arm samples (IL-8: local 2.3 [1.71-3.3] vs systemic 2.3 [1.62-2.98], P = .023; MCP-1: local 114.42 [84.29-139.05] vs systemic 103.56 [79.75-126.42], P < .0005). This was not observed in the control group. Leg samples from both patients with varicose vein and controls had higher levels of IL-6 compared to their own arm samples (patients: local 1.67 [0.82-4.48] vs systemic 1.24 [0.58-3.26], P = .002; controls: local 1.23 [0.83-1.7] vs systemic 1.03 [1.7-1.52], P = .005). No significant differences were detected with the other biomarkers. Conclusions: Blood drawn from the site of varicose veins appears to have significantly increased concentrations of IL-6, IL-8, and MCP-1 when compared to the same patient's arm blood. This supports the hypothesis that inflammation is activated from the tissues drained by the varicose veins.